Efeito de um protocolo de polimento mecânico contínuo na estabilidade de cor e rugosidade de superfície de uma resina acrílica para base de prótese dentária e dentes artificiais submetidos à fumaça de cigarro e ao café - Assis, Ellen Lima de (2020)
Introduction: The acrylic resin is widely used in the manufacture of dental prostheses. Despite its numerous advantages, it is subject to changes in its properties such as color and surface roughness over the period of use. The polishing of prosthetic surfaces is usually performed in a laboratory environment after they are polymerized, or by dentists during clinical visits. Studies evaluating the effects of continuous polishing on prosthetic materials are scarce in the literature. Objective: To evaluate in vitro the effect of a continuous mechanical polishing protocol on the color stainability and surface roughness of a denture base acrylic resin and acrylic resin artificial teeth after exposure to cigarette smoke and coffee immersion. Method: For each material, 70 specimens were divided according to the following experimental groups (n=10): DW - immersion in distilled water (control); CG - only exposure to cigarette smoke; CG + Pol - exposure to cigarette smoke + polishing; CF - only immersion in coffee solution; CF + Pol; CFCG - exposure to cigarette smoke associated with coffee immersion; CFCG + Pol. The immersion in coffee was performed for 24 days, simulating 2 years of coffee consumption. The exposure to the smoke of 10 cigarettes daily for a period of 24 days was performed using a plastic device connected to a portable suction machine. The mechanical polishing was performed by using an aluminum oxide-based polishing paste and felt wheel coupled to a manual electric motor (3000 rpm), at simulated biweekly time intervals. The surface roughness and color stainability were evaluated by using a digital contact profilometer and a portable spectrophotometer, respectively, before (T0), after 12 (T1) and 24 days (T2) of the experimental situations described. The data were analyzed by two-factor mixed ANOVA followed by the Bonferroni test for multiple comparisons (α=0.05). Results: In both materials, the associated polishing significantly reduced the changes in roughness caused by most of the experimental conditions (CF, CG, CFCG) already at T1, reaching mean values lower than those observed in the groups immersed in distilled water. The association of coffee with cigarette smoke promoted a greater impact on color stability when compared to the isolated groups (CF, CG), generating the highest mean values of ΔE00. Polishing significantly reduced the color change observed in most experimental conditions, in both materials, even for CFCG groups. Conclusion: The polishing protocol tested was able to control the color variation and the increase in surface roughness in both acrylic resin artificial teeth and denture base acrylic resin, caused by the contact with coffee and cigarette smoke, isolated or associated.